A case of subarachnoid hemorrhage due to perimedullary arteriovenous fistula with multiple feeders at the craniocervical junction cured by treating the common draining vein and a review of the literature - Sho Sato; Satoshi Fujita; Yu Hiramoto; Morito Hayashi; Naoki Kushida; Nozomi Hirai; Haruo Nakayama; Norihiko Saito; Keisuke Ito; Takatoshi Sakurai; Satoshi Iwabuchi (Brain Hemorrhages, 2023)
Objective: Craniocervical junction arteriovenous fistula (CCJ-AVF) is a rare disease, and preoperative imaging evaluation is important in developing treatment strategies due to the complexity of the vascular architecture, such as the feeding vessels, shunt points, and draining veins. In the present study, we report a case of hemorrhagic perimedullary CCJ-AVF with multiple feeding vessels in which the common single draining vein was dissected by craniotomy and completely treated. Case presentation: A 71-year-old woman presented with subarachnoid hemorrhage (Hunt & Kosnik, grade II). Cerebrovascular CTA showed no intracranial cerebral aneurysm and findings suggestive of shunt disease at the CCJ. Based on cerebral angiography, the patient was diagnosed with perimedullary CCJ AVF, with the right radicular and the left anterior spinal arteries as feeders which drain into a common dilated coronary vein through a shunt located on the ventral side of the spinal cord and then drain into the ascending and descending anterior spinal veins. Ventricular drainage was performed for acute hydrocephalus, and arteriovenous fistula was dissected electively by craniotomy on day 17 after onset. A clip was applied to the single draining vein, which had been evaluated using preoperative imaging diagnosis. Intraoperative digital subtraction angiography (DSA) confirmed the disappearance of shunt blood flow, and the surgery was completed. The follow-up DSA did not show shunt blood flow, and the patient was transferred to a rehabilitation hospital with a modified Rankin scale score of 2. Conclusion: CCJ-AVF cases often have a complex vascular architecture, and it is important to use various modalities to understand the vascular anatomy in detail and develop an appropriate treatment strategy.